The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s10549-013-2584-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential characteristics of heart, liver, and brain metastatic subsets of murine breast carcinoma

Abstract: Breast carcinoma is comprised of heterogeneous groups of cells with different metastatic potential. To develop effective therapeutic strategies targeting metastatic disease, it is crucial to understand the characteristics of breast cancer cells that enable metastasis to distant organs. 4THM breast carcinoma cells are the cells of 4T1 primary tumors that metastasized to the heart. Cells of 4THM tumors which metastasized to liver (4TLM) were previously isolated. Recently macroscopic brain metastasis in 4THM inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…CXCR4 also participates in the modulation of liver metastasis by interacting with integrins [161]. Malignant breast cells, however, also express high levels of CD44 with the highest expression occurring in cells that metastasise to the liver [162]. High levels of claudin-2 expression have also been detected in metastatic breast cells in the liver.…”
Section: Metastasis In Target Organsmentioning
confidence: 99%
“…CXCR4 also participates in the modulation of liver metastasis by interacting with integrins [161]. Malignant breast cells, however, also express high levels of CD44 with the highest expression occurring in cells that metastasise to the liver [162]. High levels of claudin-2 expression have also been detected in metastatic breast cells in the liver.…”
Section: Metastasis In Target Organsmentioning
confidence: 99%
“…These results are in agreement with previous reports suggesting that EMT generates cells that acquire malignant and stem-like traits 23, 24 . Likewise, we isolated a CD44 high /CD24 med/low cell population from 4T1m cells, which are enriched in breast CSCs 23, 33, 34 , in order to study the potential link between Qa-2 and CSCs. We found that CD44 high /CD24 med/low cells do not express Qa-2.…”
Section: Discussionmentioning
confidence: 99%
“…Hence part of VIP and majority of CGRP in our samples might be originated from infiltrating immune cells. It was previously shown that loss of peptidergic sensory neurons sensitive to capsaicin increases metastasis of breast carcinoma inducing aggressive phenotype and possibly stemness and resistance to treatment [18,20,27]. Although it was not possible to measure peptide levels in normal kidney tissues (not involved with a tumor), comparing kidney samples of different subtypes demonstrated the loss of peptidergic innervation was most obvious in kidney neighboring papillary RCC.…”
Section: Discussionmentioning
confidence: 99%